The Effective Mechanism for Decision-Making in Business Administration: Formation Conceptuality, Systemic and Intersystemic Links - Chevhanova, Vira; Hryhoryeva, Olesya; Khadartsev, Oleksandr; Miniailenko, Inna (International Journal of Engineering and Technology, 2018)
The article deals with the concept of an effective mechanism for decision-making in business administration, which the authors propose. While creating the conceptual foundations of the mechanism in the framework, authors considered: differentiations of the concepts of "management" and "administration" hierarchy of logical-structural and causal relationships of external and internal decision-making environment. Heuristic vision of the category "mechanism" is presented in conjunction with business administration specifics, for determining the sequence of stages and phases of the decision-making mechanism. Authors represent the conceptual construction of decision-making mechanism in the article, and show the decomposition of such mechanism systems, and its intersystem dependencies with visual tools. In the article authors determined, that practical implementation of the proposed concept will allow to make reasonable choices of useful business administration tools for: improving business management efficiency; improving business-processes, their functional vectors and tasks; taking into account the peculiarities of the economic environment dynamics.Â Â